Distinct and shared neuropsychiatric phenotypes in FTLD-tauopathies - Keszycki, Rachel; Kawles, Allegra; Minogue, Grace; Zouridakis, Antonia; Macomber, Alyssa; Gill, Nathan; Vu, My; Zhang, Hui; Coventry, Christina; Rogalski, Emily; Weintraub, Sandra; Mesulam, M-Marsel; et al. (Frontiers in Aging Neuroscience, 2023)
Frontotemporal lobar degeneration (FTLD) with tau pathology (FTLD-tau) commonly causes dementia syndromes that include primary progressive aphasia (PPA) and behavioral variant frontotemporal dementia (bvFTD). Cognitive decline in PPA and bvFTD is often accompanied by debilitating neuropsychiatric symptoms. In 44 participants with PPA or bvFTD due to autopsy-confirmed FTLD-tau, we characterized neuropsychiatric symptoms at early and late disease stages and determined whether the presence of certain symptoms predicted a specific underlying FTLD-tauopathy. Participants completed annual research visits at the Northwestern University Alzheimer’s Disease Research Center. All participants had an initial Global Clinical Dementia Rating (CDR) Scale score ≤ 2, and neuropsychiatric symptoms were evaluated via the Neuropsychiatric Inventory-Questionnaire (NPI-Q). We assessed the frequency of neuropsychiatric symptoms across all participants at their initial and final visits and performed logistic regression to determine whether symptoms predicted a specific FTLD-tau pathologic diagnosis. Across the FTLD-tau cohort, irritability and apathy were most frequently endorsed at initial and final visits, respectively, whereas psychosis was highly uncommon at both timepoints. Irritability at initial visit predicted greater odds of a 4-repeat compared to a 3-repeat tauopathy (OR = 3.95, 95% CI = 1.10–15.83, p < 0.05). Initial sleep disturbance predicted greater odds of progressive supranuclear palsy (PSP) compared to other FTLD-tau subtypes (OR = 10.68, 95% CI = 2.05–72.40, p < 0.01). Appetite disturbance at final evaluation predicted lower odds of PSP (OR = 0.15, 95% CI = 0.02–0.74, p < 0.05). Our findings suggest that characterization of neuropsychiatric symptoms can aid in the prediction of underlying FTLD-tauopathies. Given considerable pathologic heterogeneity underlying dementias, neuropsychiatric symptoms may be useful for differential diagnosis and treatment planning.